Assessing Nurse’s Knowledge of Drug Dose Calculation: A Cross-Sectional Study in a Private Hospital in Lahore - Rafique, Shamas; Najam, Shahroz; Arif, Abdur Rehman; Liaqat, Mishal; Samson, Carol (Biological and Clinical Sciences Research Journal, 2025)
Accurate drug dose calculation is a critical competency for nurses to ensure safe and effective patient care. Medication errors, often linked to poor dosage knowledge, pose significant risks, particularly in developing countries like Pakistan. This study aims to assess the knowledge of drug dose calculations among registered nurses at a private tertiary care hospital in Lahore. Objective: To evaluate the level of knowledge regarding drug dose calculations among registered nurses and identify areas requiring educational intervention. Methods: A descriptive cross-sectional study was conducted from January to April 2025 at Gulab Devi Hospital, Lahore. A total of 126 registered nurses were selected using a non-probability convenience sampling technique. Data were collected via a self-administered questionnaire comprising demographic details and 20 multiple-choice questions on drug dose calculation. Each correct response earned one point, with knowledge categorized as poor (1–5), satisfactory (6–10), good (11–15), or excellent (16–20). Data were analyzed using SPSS version 27. Results: The majority of participants were female (88.1%) and aged 20–35 years (65.1%). Most held a General Nursing Diploma (55.6%), and one-third had over 10 years of experience. The mean knowledge score was 11.52 ± 4.93. Over half (55.6%) of the nurses demonstrated satisfactory knowledge, 33.3% had excellent knowledge, 8.7% showed good knowledge, while 2.4% had poor knowledge. High accuracy was noted in basic unit conversions, while lower performance was observed in complex calculations such as dilution and weight-based dosages. Conclusion: The findings indicate moderate competence in drug dose calculations among nurses, with significant room for improvement in complex clinical scenarios. Educational interventions, such as structured training and the use of digital tools, are recommended to enhance dosage calculation competencies and reduce medication errors.